The Role Of Facebook In Enhancing Meaning-Making Among Pre-University Students - Nadarajan, Sheela (2019)
The success or failure of pupils in school in all subjects depends on their ability to read and understand. In order to understand, the readers should be able to make meaning out of what they read. Within the Malaysian context, reading is an activity that is fast losing its appeal as other forms of media gain popularity especially the Web 2.0 technologies. Bearing this in mind the researcher experimented on the use of Facebook as a platform to read and make meaning . The main objective of this study was to investigate students‟ ability in reading and make meaning via Facebook. A total of 22 students from pre-university class were chosen to take part in this study. The task was to read and understand articles via online . This study created a reason for students to read. At the same time, they make meaning of what they read, review the content of the article chosen and relate what they had learned to what they already know. Using a qualitative approach, data was obtained from the thematic analysis showed that the students exhibited positive reading habits and engaged in learner centered activities. The main findings from this study showed that the use of Facebook could help students in making meaning of what they have read. Next, this activity also helped to inculcate collaboration and share of ideas among participants where the students shared various types of information from the internet. They also discussed choice of words to use especially when replying to their friends.